Students’ perspectives on racism and anti-racism in physical education: a systematic review - Abel, Lucas; Galle, Annette Chidinma; Ziehmann, Laszlo; Vogt, Tobias (Frontiers in Sociology, 2024)
Sports, with their various social manifestations, exhibit racist structures and incidents. Physical education (PE) has the potential to serve as an environment to combat racism, but it can also perpetuate and (re)produce racist attitudes and behaviors. This study aimed to conduct a systematic review of national (German) and international literature concerning racism and anti-racism within the context of PE specifically from a students’ perspective. The research methodology followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standard and encompassed a four-step process: (1) searching 11 electronic databases using 70 keyword combinations in both German and English; (2) selecting studies based on five predetermined inclusion criteria; (3) evaluating the quality of selected studies using established appraisal tools; and (4) conducting descriptive and template analyses. Of 5,213 publications, 16 met the inclusion criteria, demonstrating diverse theoretical frameworks and methodological approaches. Five themes were constructed: “How racism is understood” (1); “What students experience,” encompassing discriminatory incidents in PE, sports, and daily life classified as racial stereotypes, prejudices, and everyday racism (2); and “What physical education teachers (3)/Institutions (4)/researchers (5) can and should do.” These themes provided recommendations for teachers, institutions, and researchers, including training and curriculum reforms. While valuable international literature was identified, no German PE specific publications were found emphasizing the necessity of a local (German) survey to comprehend students’ experiences, knowledge, and potential for anti-racism efforts. Such insights are crucial for shaping teacher-related training programs and policy demands in an informed and targeted manner.